2013
DOI: 10.5858/arpa.2012-0617-oa
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Population-Based Comparison of HER2 Immunohistochemistry and Fluorescence In Situ Hybridization in Breast Carcinomas: Impact of 2007 American Society of Clinical Oncology/ College of American Pathologists Criteria

Abstract: Context.—In 2007 the American Society of Clinical Oncology/College of American Pathologists made new recommendations for HER2 testing and redefined HER2 positivity. Objective.—To analyze results from simultaneous HER2 testing with immunohistochemistry and fluorescence in situ hybridization (FISH) in 2590 invasive breast carcinomas between 2002 and 2010, using 2 scoring systems. Design.—Cases from between 2002 and 2006 were scored by using original US Food and Drug Administration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 28 publications
12
52
1
1
Order By: Relevance
“…Although the stricter criteria of 30% The close association between HER2/neu gene amplification and protein overexpression in breast carcinomas was evident by the higher FISH ratios as well as HER2/neu copy numbers with higher HER2/neu membranous immunoreactivity as confirmed by other studies (Tables 5 and 6). 18 In addition, most IHC2þ cases were negative for HER2/neu FISH amplification (81.6% (418 of 512; Table 1), which was a finding similar to that of others. 16,18 However, the number of equivocal IHC/negative FISH cases decreased with the revised 2013 ASCO/CAP guidelines because of an increase in the number of negative FISH cases with an average HER2/neu copy number of at least 4.0 but less than 6.0 that were reclassified to equivocal.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Although the stricter criteria of 30% The close association between HER2/neu gene amplification and protein overexpression in breast carcinomas was evident by the higher FISH ratios as well as HER2/neu copy numbers with higher HER2/neu membranous immunoreactivity as confirmed by other studies (Tables 5 and 6). 18 In addition, most IHC2þ cases were negative for HER2/neu FISH amplification (81.6% (418 of 512; Table 1), which was a finding similar to that of others. 16,18 However, the number of equivocal IHC/negative FISH cases decreased with the revised 2013 ASCO/CAP guidelines because of an increase in the number of negative FISH cases with an average HER2/neu copy number of at least 4.0 but less than 6.0 that were reclassified to equivocal.…”
Section: Resultssupporting
confidence: 83%
“…18 In addition, most IHC2þ cases were negative for HER2/neu FISH amplification (81.6% (418 of 512; Table 1), which was a finding similar to that of others. 16,18 However, the number of equivocal IHC/negative FISH cases decreased with the revised 2013 ASCO/CAP guidelines because of an increase in the number of negative FISH cases with an average HER2/neu copy number of at least 4.0 but less than 6.0 that were reclassified to equivocal. In fact, the number of equivocal FISH cases increased from 0.7% (4 of 590) to 9.5% (56 of 590) (Table 4) as confirmed by Pu et al 33 In addition, equivocal IHC/equivocal FISH cases also increased from 0.7% (4 of 590) to 8.3% (49 of 590) ( Tables 1 and 2).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Our study results indicate that this guideline change may have resulted in reclassifying approximately 5.9% of IHC3+ tumors to IHC2+, which is consistent with other reports of increased IHC2+ tumors during this time period 22,23. Additionally, although not significant, the proportion of HER2+ patients did decrease after guideline publication (4.2%), which is consistent with other reports documenting a 3% difference 23.…”
Section: Discussionsupporting
confidence: 91%
“…5 It was identified from a retrospective review of 2590 cases that IHC and FISH had a concordance rate of 96%, which is better with negative IHC. 23 Two basic points in the recommendations are worth noting; firstly, diagnosis HercepTest score >2+, and makes it perhaps illogical to perform an ISH test on a specimen if the IHC is negative. It is pertinent to emphasize that this appraised study reported a discrepancy of 18% (31/174), which translates to a concordance of 82%.…”
Section: Outcome -The Appraisal and Discussionmentioning
confidence: 99%